Therapeutic strategies for glucose transporter 1 deficiency syndrome. Issue 9 (28th August 2019) - Tang, Maoxue; Park, Sarah H.; De Vivo, Darryl C.; Monani, Umrao R.
Abstract: Proper development and function of the mammalian brain is critically dependent on a steady supply of its chief energy source, glucose. Such supply is mediated by the glucose transporter 1 (Glut1) protein. Paucity of the protein stemming from mutations in the associated SLC2A1 gene deprives the brain of glucose and triggers the infantile‐onset neurodevelopmental disorder, Glut1 deficiency syndrome (Glut1 DS). Considering the monogenic nature of Glut1 DS, the disease is relatively straightforward to model and thus study. Accordingly, Glut1 DS serves as a convenient paradigm to investigate the more general cellular and molecular consequences of brain energy failure. Here, we review how Glut1 DS models have informed the biology of a prototypical brain energy failure syndrome, how these models are facilitating the development of promising new treatments for the human disease, and how important insights might emerge from the study of Glut1 DS to illuminate the myriad conditions involving the Glut1 protein.